Pengaruh Dari Kepemimpinan Transformasional Terhadap Komitmen Organisasi Taruna Utama Prodi Manajemen Pemasyarakatan B - Dito Febriyolas; Padmono Wibowo (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Found that the relationship between transformational leadership and affective commitment is transmitted through perceived work impact. In this research, the population is cadets of the Correctional Science Polytechnic class 55 Correctional Management Study Program class B with a sample of 30 cadets.The method of collecting data for this study is to distribute questionnaire links or questionnaires using google form randomly which are then processed using SPSS v27 64Bit. the result is HO is rejected and there is a significant effect of variable x on y